2020
DOI: 10.1186/s13550-020-0601-y
|View full text |Cite
|
Sign up to set email alerts
|

Standardized image quality for 68Ga-DOTA-TATE PET/CT

Abstract: Background: Positron emission tomography (PET) imaging with 68 Gallium labeled somatostatin analogues (68 Ga-DOTA-SSA) plays a key role in neuroendocrine tumor management. The impact of patient size on PET image quality is not well known for PET imaging with 68 Ga-DOTA-SSA. The aim of this study is to propose a dose regimen based on patient size that optimizes image quality and yields sufficient image quality for diagnosis. Methods: Twenty-one patients (12 males, 9 females) were prospectively included for 68 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…The fits of SNR norm with different parameters showed that both the quadric and linear fitting with BMI had the highest R 2 (0.68 and 0.69, respectively). Other parameters, such as the body mass, height, body mass per height, lean body mass, fat mass and body surface area showed a lower value of R 2 than the parameters discussed in previous studies [15,16]. Based on the results, a linear fit with BMI was selected.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The fits of SNR norm with different parameters showed that both the quadric and linear fitting with BMI had the highest R 2 (0.68 and 0.69, respectively). Other parameters, such as the body mass, height, body mass per height, lean body mass, fat mass and body surface area showed a lower value of R 2 than the parameters discussed in previous studies [15,16]. Based on the results, a linear fit with BMI was selected.…”
Section: Discussionmentioning
confidence: 97%
“…If the SNR in the liver is normalized by the square root of the DTP, it can be assumed to be independent of the injected activity and the acquisition time (Eq. 5) [16]. Therefore, SNR norm can be regarded as a function of various patientdependent parameters and investigated in the study.…”
Section: Image Analysismentioning
confidence: 99%
“…This ideally provides the opportunity for an activity range of 68 Ga-satoreotide trizoxetan (100-200 MBq) to be prescribed, regardless of body weight. By contrast, 68 Ga-labelled SSTR2 agonists require dosing per body mass (10,11,16). In a recent prospective study from the Netherlands conducted among 21 patients with NETs who underwent whole-body 68 Ga-DOTATATE PET/CT, Cox and colleagues reported that, of all patient-dependent parameters, body mass showed the strongest correlation (coefficient of determination of 0.60) with normalised signal-to-noise ratio (16).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, 68 Ga-labelled SSTR2 agonists require dosing per body mass (10,11,16). In a recent prospective study from the Netherlands conducted among 21 patients with NETs who underwent whole-body 68 Ga-DOTATATE PET/CT, Cox and colleagues reported that, of all patient-dependent parameters, body mass showed the strongest correlation (coefficient of determination of 0.60) with normalised signal-to-noise ratio (16). Importantly, the absence of a weight-dependent effect represents a practical advantage for 68 Ga-satoreotide trizoxetan, as an administered activity within a predetermined range instead of a weight-based administered activity is not only more convenient but also reduces the possibility of dosing errors.…”
Section: Discussionmentioning
confidence: 99%
“…And ultra-low dose (0.37 MBq/kg) injected activity of 18 F-FDG could achieve relevant kinetic metrics and comparable image quality compared with that of full-activity imaging [11]. Besides, using conventional dose-regimen, the acquisition time could be significantly shorter within 2 min for a sufficient image quality of 18 F-FDG PET/CT [12].…”
mentioning
confidence: 99%